Chapter 5 A Motor-Flight through North Africa - Kovács, Ágnes Zsófia (Taylor & Francis, 2024)
Edith Wharton was not only the author of novels and short stories but also of drama, poetry, autobiography, interior decoration, and travel writing. This study focuses on Wharton’s symbolic representations of architecture in her travel writings. It shows how a network of allusions to travel writing and art history books influenced Wharton’s representations of architectural and natural spaces. The book demonstrates Wharton’s complex relationship to works of art historians (John Ruskin, Émile Mâle, Arthur C. Porter) and travel authors (Wolfgang Goethe, Henry Adams, Henry James) in the trajectory of her travel writing. Kovács surveys how the acknowledgment of Wharton’s sources sheds light both on the author’s model of aesthetic understanding and scenic architectural descriptions, and how the shock of the Great War changed Wharton’s travel destinations but not her symbolic view of architecture as a mediator of things past. Wharton’s symbolic representations of architecture provide a new key to her travel writings.